PIMPIN to cultivate prolific writers - Amira, Abdullah (2020)
Kuantan, 28 September 2020 - To improve skills in the field of writing and publishing, and to produce more writers, for the first time the Islamic and Human Development Centre (PIMPIN), Universiti Malaysia Pahang (UMP) organized a Book Writing and Publication Workshop.